Skeletal Muscle-Specific Methyltransferase METTL21C Trimethylates p97 and Regulates Autophagy-Associated Protein Breakdown - Janica Lea Wiederstein; Hendrik Nolte; Stefan Günther; Tanja Piller; Martina Baraldo; Sawa Kostin; Wilhelm Bloch; Natalie Schindler; Marco Sandri; Bert Blaauw; Thomas Braun; Soraya Hölper; et al. (Cell Reports, 2018)
Summary: Protein aggregates and cytoplasmic vacuolization are major hallmarks of multisystem proteinopathies (MSPs) that lead to muscle weakness. Here, we identify METTL21C as a skeletal muscle-specific lysine methyltransferase. Insertion of a β-galactosidase cassette into the Mettl21c mouse locus revealed that METTL21C is specifically expressed in MYH7-positive skeletal muscle fibers. Ablation of the Mettl21c gene reduced endurance capacity and led to age-dependent accumulation of autophagic vacuoles in skeletal muscle. Denervation-induced muscle atrophy highlighted further impairments of autophagy-related proteins, including LC3, p62, and cathepsins, in Mettl21c−/− muscles. In addition, we demonstrate that METTL21C interacts with the ATPase p97 (VCP), which is mutated in various human MSP conditions. We reveal that METTL21C trimethylates p97 on the Lys315 residue and found that loss of this modification reduced p97 hexamer formation and ATPase activity in vivo. We conclude that the methyltransferase METTL21C is an important modulator of protein degradation in skeletal muscle under both normal and enhanced protein breakdown conditions. : Wiederstein et al. describe the skeletal muscle methyltransferase Mettl21c. They found that ablation of Mettl21c in mice results in muscle weakness and disturbance of the protein degradation machinery. Those changes are hallmarks of multisystem proteinopathies. They demonstrate that Mettl21c modulates p97 activity, which is frequently mutated in human patients with muscle weakness. Keywords: methyltransferases, skeletal muscle, p97, atrophy, autophagy